Value proposition design at training and consulting services company in Sharia financial banking Lampung Province at CV. Acceleration Indonesia Juara - Hengki Yuliansyah (Goodwood Publishing, 2024)
Purpose: This study aims to identify the causes of the existing business performance gap and design a value proposition for training and consulting services companies in the Sharia financial sector in Lampung Province at CV. Akselerasi Indonesia Juara. Research Methodology: This research is exploratory, beginning with observations of phenomena and problems and developing initial ideas about them, which then move towards refining the research questions. Results: CV Akselerasi Indonesia Juara has created a sustainable program to provide training services. Because BPRS likes the service, they do not like it when the service is limited to the classroom. Ongoing programs can be created by providing alumni forums, sharing forums, and even ongoing programs. Conclusions: CV Akselerasi Indonesia Juara should extend its training beyond classrooms through sustainable engagement programs while strengthening its divisions and innovating post-pandemic to enhance competitiveness in the sharia financial sector of Lampungn. Limitations: The company, AKIRA, provides training and consulting services to various institutions and companies, including UKMs, and has three divisions: Public Training, In-House Training, and CCC (Coaching, Consulting & Co-management). Contribution: The company faced challenges in developing its business due to the COVID-19 pandemic, which disrupted the training and consulting services industry.